The system for near-real time air pollution monitoring over cities based on the Sentinel-5P satellite data - Mykhailo Savenets; Andrii Oreshchenko; Liudmyla Nadtochii (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2022)
Introduction. Air pollution heterogeneity and rapid urbanization impose numerous constraints on available near-surface air quality monitoring. The solution for effective warning comes with the integration of different data, including remote sensing. Satellite data cannot answer whether dangerous pollution levels are observed; however, it provides a complete picture and may detect air pollution transportation towards or away from cities. The possibilities for effective near-real time (NRTI) monitoring have significantly improved with the launch of the Sentinel-5P satellite. The study aimed to describe the developed system for NRTI air pollution monitoring over Kharkiv, Kryvyi Rig, Kyiv, and Odesa based on NO2 and CO data derived from the Sentinel-5P satellite.